Effect of Weight Maintenance on Symptoms of Knee Osteoarthritis in Obese Patients: A Twelve‐Month Randomized Controlled Trial. Issue 5 (May 2015) - Christensen, Robin; Henriksen, Marius; Leeds, Anthony R.; Gudbergsen, Henrik; Christensen, Pia; Sørensen, Tina J.; Bartels, Else M.; Riecke, Birgit F.; Aaboe, Jens; Frederiksen, Rikke; Boesen, Mikael; Lohmander, L. Stefan; et al.
<x xml:space="preserve">Abstract</x> Objective To compare results of obese patients with knee osteoarthritis (OA) who, after an intensive weight loss regimen, received 1 year of either dietary support (D), a knee‐exercise program (E), or "no attention" (C; control group). Methods We conducted a randomized, 2‐phase, parallel‐group trial. A total of 192 obese participants with knee OA were enrolled; the mean age was 62.5 years and 81% were women with a mean entry weight of 103.2 kg. In phase 1, all participants were randomly assigned to 1 of 3 groups and began a dietary regimen of 400–810 and 1, 250 kcal/day for 16 weeks (2 8‐week phases) to achieve a major weight loss. Phase 2 consisted of 52 weeks' maintenance in either group D, E, or C. Outcomes were changes from randomization in pain on a 100‐mm visual analog scale, weight, and response according to the Outcome Measures in Rheumatology‐Osteoarthritis Research Society International criteria. Results Mean weight loss for phase 1 was 12.8 kg. After 1 year on maintenance therapy, the D group sustained a lower weight (11.0 kg, 95% confidence interval [95% CI] 9.0, 12.8 kg) than those in the E (6.2, 95% CI 4.4, 8.1 kg) and C (8.2, 95% CI 6.4, 10.1 kg) groups (P = 0.002 by analysis of covariance [ANCOVA]). Adherence was low in the E group. All groups had statistically significant pain reduction (D: 6.1; E: 5.6; and C: 5.5 mm) with no difference between groups (P = 0.98 by ANCOVA). In each group 32 (50%), 26 (41%), and 33 (52%) participants responded to treatment in the D, E, and C groups, respectively, with no statistically significant difference in the number of responders (P = 0.41). Conclusion A significant weight reduction with a 1‐year maintenance program improves knee OA symptoms irrespective of maintenance program.